2013
DOI: 10.1093/schbul/sbt178
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cortical Expression of GABA-Related Genes in Schizophrenia: Illness Progression vs Developmental Disturbance

Abstract: Results: Levels of vGAT and GABRA1, but not of GAT1, messenger RNAs (mRNAs) were lower in the PFC of the schizophrenia subjects. As previously reported, levels of GAD67, parvalbumin, and somatostatin, but not of calretinin, mRNAs were also lower in these subjects. Neither illness duration nor age accounted for the levels of the transcripts with altered expression in schizophrenia. In monkey PFC, developmental changes in expression levels of many of these transcripts were in the opposite direction of the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 63 publications
11
107
3
2
Order By: Relevance
“…Adult mice with GAD1 gene expression deficits in restricted interneuron populations have distinct molecular and behavioral dysfunction depending on the affected cell type Kvitsiani et al, 2013;Schmidt et al, 2013). These data provide functional context to postmortem studies that consistently implicate diverse interneuron cell types in schizophrenia (Hashimoto et al, 2003(Hashimoto et al, , 2008aHoftman et al, 2013;Iritani et al, 2000;Kuromitsu et al, 2001;Maldonado-Aviles et al, 2009;Mellios et al, 2009;Morris et al, 2008;Volk et al, 2012) and suggest that GABAergic gene expression deficits seen in post-mortem studies of patients with schizophrenia actively contribute to important aspects of brain development and behavior (Lewis et al, 2005;Marin, 2012;Schmidt and Mirnics, 2012).…”
Section: Gene Effects Converge Onto Gaba System Developmentmentioning
confidence: 78%
See 2 more Smart Citations
“…Adult mice with GAD1 gene expression deficits in restricted interneuron populations have distinct molecular and behavioral dysfunction depending on the affected cell type Kvitsiani et al, 2013;Schmidt et al, 2013). These data provide functional context to postmortem studies that consistently implicate diverse interneuron cell types in schizophrenia (Hashimoto et al, 2003(Hashimoto et al, , 2008aHoftman et al, 2013;Iritani et al, 2000;Kuromitsu et al, 2001;Maldonado-Aviles et al, 2009;Mellios et al, 2009;Morris et al, 2008;Volk et al, 2012) and suggest that GABAergic gene expression deficits seen in post-mortem studies of patients with schizophrenia actively contribute to important aspects of brain development and behavior (Lewis et al, 2005;Marin, 2012;Schmidt and Mirnics, 2012).…”
Section: Gene Effects Converge Onto Gaba System Developmentmentioning
confidence: 78%
“…However, this does not mean that the majority of interneurons are unaffected by the disease process. Reductions of interneuronal-expressed genes NPY, SST, CCK, and PV have been found repeatedly in the cortex of subjects with schizophrenia in post-mortem studies (Hashimoto et al, 2003(Hashimoto et al, , 2008aHoftman et al, 2013;Ikeda et al, 2004;Iritani et al, 2000;Kuromitsu et al, 2001;Maldonado-Aviles et al, 2009;Mellios et al, 2009;Volk et al, 2012). Deleting GAD1 in animal models causes catastrophic effects on development by almost completely reducing brain GABA content and is not compatible with life (Asada et al, 1997).…”
Section: Gene Effects Converge Onto Gaba System Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the papers associated to neurodevelopment, one study concluded that GABA related mRNA disturbances in schizophrenia seem to not be related with illness chronicity, but may be the consequence of blunted or incomplete neurodevelopment 41 . The differences found between schizophrenia subjects and control go in the opposite direction of changes in expression during development (for example, vGAT, GAD 67 and parvalbumin mRNA levels increased during postnatal development, whereas they were decreased in schizophrenia subjects compared to control).…”
Section: Neurodevelopmentmentioning
confidence: 99%
“…Genetic factors account for around 22% of the variation in gene expression between individuals, with the remaining variation due to environmental and stochastic factors (127)(128)(129). The genome-wide analysis of gene expression, known as transcriptomics, has identified genes and molecular processes underlying a range of brain-related traits (14,130,131) and informed the development of gene expression panels for the classification and diagnosis of disease (132)(133)(134).…”
Section: Mapping Complex Traits With Genome-wide Gene Expression Datamentioning
confidence: 99%